ANALISIS PENGGUNAAN GLIBENKLAMID DAN GLIMEPIRID BERDASARKAN PERESEPAN OBAT MENGGUNAKAN METODE ATC/DDD) - Elva Asmiati; Shafelia Nata Aji Kusuma; Ika Ratna Hidayati; Rizka Novia Atmadani (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
Diabetes Mellitus is a non-contagious disease in which insulin cannot be produced optimally by the pancreas, characterized by hyperglycemia. Glibenclamide and glimepiride are sulfonylurea antidiabetic drugs. To analyze the use of Glibenclamide and Glimepirid drugs at the Sekupang Public Health Center in 2020 using the ATC/DDD method. The result of DDD/1000 KPRJ/Day Glibenclamide 5 mg was 10.29 mg for the highest on April, and the lowest was 0.57 mg on February. The one-year average was 2.97 mg. The result of DDD//1000 OPV/Day Glimepiride 2 mg was 16.80 mg is the highest on February, and the lowest was 2.79 mg on June. The one-year average was 6.77 mg. The results of DDD/1000 KPRJ/Day Glimepiride 4 mg were highest on October 23,48 mg, and the lowest was on January 3.45 mg, with 13.15 mg average per year. The one-year average of DDD value of Glibenclamide 5 mg does not surpass the 10 mg WHO DDD value, so it can be concluded that the use of Glibenclamide has not been widely used in the community. For Glimepiride 2 mg and 4 mg, the DDD value obtained exceeds the WHO DDD value of 2 mg, it can be concluded that Glimepirid is widely used in the community.